Green hydrogen production by proton exchange membrane electrolysis: a sustainable approach - Ahmed, Afaf (International Journal of Engineering and Technology, 2024)
Extending worldwide request for sustainable energy can be attributed to two con-templations: the decrease of conventional energy sources and climate change. Proton exchange membrane (PEM) electrolysis generates green hydrogen, as attainable sub-stitute for clean and economical energy. In this study the 7,9 UN sustainable goals were applied for the proton exchange membrane (PEM) electrolysis, that split water to oxygen and hydrogen as clean fuel. The goals applied though out all the PEM electrolysis part, to ensure that the method of generating hydrogen through PEM is a sustainable approach for the future clean fuel, within its production with zero carbon emission and within its application in the fuel cells. Results approved that PEM electrolysis offers fast reaction times during load changes, excellent efficiency, and modular stability. It consumes less clean energy and runs at lower pressures and temperatures, which reduces system costs which were aligned with the goals 7. The Current developments in catalysts and membrane materials approved the durability and efficiency which represents UN goal No 9. for the sustainable industry innovative resources for our future cities.